Ethical Challenges of E-Governance: Insights from Bangladesh - Rajib Chandra Das (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2026)
Backgrounds: Globally, e-government has grown in importance as a tool for contemporary administration. Bangladesh started this journey with high hopes to make government services better and easier for people. But along with the good changes, many ethical problems have come up. Objectives: This paper talks about moral problems in detail and suggests ways to fix them. The first part of the paper talks about what e-government is and why ethics are important in this area. After that, it talks about how e-government has grown in Bangladesh. And what problems have arisen. Finally, it provides suggestions on how to resolve these moral issues. Methodology: This study examines the ethical challenges of e-governance in Bangladesh using a descriptive qualitative approach. Data was collected through documentation studies and literature reviews, analyzing official documents, reports, academic publications, and government websites. Source triangulation was employed to ensure data validity and reliability. Findings: Findings reveal that despite significant progress, including the National Web Portal, over 8,000 Union Digital Centers, and mobile services—seven ethical challenges persist: digital divide, weak privacy protections, transparency gaps, digital corruption, cybersecurity threats, low digital literacy, and exclusion of marginalized groups. Conclusions: The foremost conclusion is that e-government will create more problems than it can resolve if good moral values and stringent regulations do not back it. The paper recommends that authorities prioritize equal access, robust data protection laws, improved employee training, and transparent accountability mechanisms. Only then can e-government contribute to national development in a just and equitable manner.